Prevalence of Metabolic Syndrome and Its Association with Sociodemographic Characteristics in Participants of a Public Chronic Disease Control Program in Medellin, Colombia, in 2018 (2020)
Metabolic syndrome has increased to epidemic levels in low- and middleincome countries. The knowledge on metabolic syndrome and its related diseases constitutes a clinical, epidemiological, and economic challenge of great relevance.